Changes of Soil Phosphorus Fractionation According to pH in Red Soils of China: An Incubation Experiment - Xiaoyang, Zhou; Minggang, Xu; Boren, Wang; Zejiang, Cai; Gilles, Colinet (Communications in Soil Science and Plant Analysis, 2018)
Phosphorus (P) deficiency is one of the main problems limiting crop growth in red soils of southern China. The primary objective of this study was to examine P availability as a function of soil acidity. Soils were sampled from a long-term fertilization experiment and are referred as low-P (No P fertilization) and high-P (120 kg P 2 O 5 ha -1 ). Both low-P and high-P treatments were incubated adjusting soil pH to seven levels from 3.0 to 6.5 for 10, 20, 30 and 45 days. The pH, DIP, and Olsen-P were determined after each incubation period, and inorganic P fractions were measured at the end of incubation. For both low-P and high-P treatments, DIP decreased with rising pH value and increased with decreasing soil pH. Olsen-P, Ca-P (Ca 2 -P, Ca 8 -P, and Ca 10 -P) and Al-P increased significantly with soil pH in low-P treatment. In high-P, Olsen-P increased with pH between 3.4 and 5.0 and was stable at higher pH. Moreover, Ca-P and Al-P increased significantly but Fe-P decreased with soil pH increase. The redundancy analysis showed that Ca-P, Al-P, and pH had positive effects on Olsen-P, but Occluded-P showed a negative correlation with Olsen-P in both soils. Our results confirmed that soil P availability was influenced by pH and that the changes in DIP and Olsen-P were linked to changes of inorganic fractions from occluded to Ca- and Al-bound forms. Managing soil acidity is a key issue regarding the availability of P in red soils of China and our results suggest that at least a pH of 5.0 should be targeted.